A Strategy for Rapid Acquisition of the β-D-Fructofuranosidase Gene through Chemical Synthesis and New Function of Its Encoded Enzyme to Improve Gel Properties during Yogurt Processing - Zhou Chen; Yimei Shen; Jiangqi Xu (Foods, 2023)
A chemical gene synthesis strategy was developed in order to obtain β-D-fructofuranosidase, and a novel gene, AlFFase3, was characterized from Aspergillus luchuensis and expressed in Escherichia coli. The recombinant protein was purified, showing a molecular mass of 68.0 kDa on SDS-PAGE, and displaying a specific activity towards sucrose of up to 771.2 U mg−1, indicating its exceptional enzymatic capacity. AlFFase3 exhibited stability between pH 5.5 and 7.5, with maximal activity at pH 6.5 and 40 °C. Impressively, AlFFase3, as a soluble protein, was resistant to digestion by various common proteases, including Flavourzyme, acidic protease, pepsin, neutral protease, Proteinase K, alkaline proteinase, and trypsin. AlFFase3 also demonstrated significant transfructosylation activity, with a yield of various fructooligosaccharides up to 67%, higher than almost all other reports. Furthermore, we demonstrated that the addition of AlFFase3 enhanced the growth of probiotics in yogurt, thereby increasing its nutritional value. AlFFase3 also improved the formation of yogurt gel, reducing the gel formation time and lowering the elasticity while increasing its viscosity, thereby improving the palatability of yogurt and reducing production costs.